2014
DOI: 10.1128/mcb.00040-14
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Activation of Conventional and Novel Protein Kinases C through Differential Translocation Patterns

Abstract: Activation of the two ubiquitous families of protein kinases, protein kinase A (PKA) and protein kinase C (PKC), is thought to be independently coupled to stimulation of G␣ s and G␣ q , respectively. Live-cell confocal imaging of protein kinase C fluorescent protein fusion constructs revealed that simultaneous activation of G␣ s and G␣ q resulted in a differential translocation of the conventional PKC␣ to the plasma membrane while the novel PKC␦ was recruited to the membrane of the endoplasmic reticulum (ER). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 83 publications
1
30
0
Order By: Relevance
“…The latter aspect is likely to be relevant for the rather fragile mouse RBCs. Confocal imaging was performed as previously described [24], in detail we used a multibeam array scanner (Infinity-4, VisiTech Int., Sunderland, UK) with a 491 nm DPSS laser (Calypso, Cobolt, Solna, Sweden). The confocal scanner was attached to an inverted microscope (TE2000-U, Nikon, Tokyo, Japan) utilising a 60x objective.…”
Section: Imagingmentioning
confidence: 99%
“…The latter aspect is likely to be relevant for the rather fragile mouse RBCs. Confocal imaging was performed as previously described [24], in detail we used a multibeam array scanner (Infinity-4, VisiTech Int., Sunderland, UK) with a 491 nm DPSS laser (Calypso, Cobolt, Solna, Sweden). The confocal scanner was attached to an inverted microscope (TE2000-U, Nikon, Tokyo, Japan) utilising a 60x objective.…”
Section: Imagingmentioning
confidence: 99%
“…By coexpression of fluorescent protein markers of intracellular membranes, we attempted to understand the process of PKCδ translocation in living cells. Quantitative co-localization analysis of its subcellular targeting revealed that following ATP stimulation the endoplasmic reticulum (ER) membrane was the main target for PKCδ recruitment rather than Golgi or mitochondrial membranes [18]. Other nPKC subfamily member, e.g.…”
Section: Physiological Stimuli Induce Npkc Targeting To the Er Membranementioning
confidence: 99%
“…By employing a combination of multiple pharmacological and molecular biological methods with optical techniques, we dissected the cAMP/Epac/PLCε signalling pathway and demonstrated that the activation of PLCε accelerates the production of DAG at the ER membrane, DAG ER [18]. DAG ER can be specifically recognized by the C1 domain of PKCδ and recruits PKCδ to the ER membrane (X. Hui, G. Reither, L. Kaestner and P. Lipp, unpublished work).…”
Section: Specific Dag Generation At the Er Membrane By A Camp/epac/plmentioning
confidence: 99%
See 1 more Smart Citation
“…6 -9, compartment-dependent translocation of PKC isoforms to the plasma membrane, the nuclear membrane, or the Golgi complex determines specific intracellular responses by placing PKC isoforms in proximity to their interaction partners. By using genetically encoded FRET-based sensors of organelle-specific PKC activity, recent studies provide evidence that location-specific DAG production enables recruitment of PKC isoforms to different intracellular membranes (10,11). Spatially restricted activation of components downstream of G q has been shown to modulate several types of ion channels in a receptor species-dependent fashion, e.g.…”
mentioning
confidence: 99%